2011
DOI: 10.1128/aac.00065-11
|View full text |Cite
|
Sign up to set email alerts
|

Sitamaquine Overcomes ABC-Mediated Resistance to Miltefosine and Antimony inLeishmania

Abstract: Although oral miltefosine represented an important therapeutic advance in the treatment of leishmaniasis, the appearance of resistance remains a serious threat. LMDR1/LABCB4, a P-glycoprotein-like transporter included in the Leishmania ABC (ATP-binding cassette) family, was the first molecule shown to be involved in experimental miltefosine resistance. LMDR1 pumps drugs out of the parasite, thereby decreasing their intracellular accumulation. Sitamaquine, another promising oral drug for leishmaniasis, is curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…Finally, it raises concern about the impact of such major molecular adaptations on the outcome of the few available drugs that are implemented in the Indian subcontinent. This is even more concerning, when one is reminded that both Sb and miltefosine exploit the same efflux pump (40). Further work is required to understand if the increasing treatment failure rate of miltefosine in the Indian subcontinent is the consequence of the heritage of the antimonials (41).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it raises concern about the impact of such major molecular adaptations on the outcome of the few available drugs that are implemented in the Indian subcontinent. This is even more concerning, when one is reminded that both Sb and miltefosine exploit the same efflux pump (40). Further work is required to understand if the increasing treatment failure rate of miltefosine in the Indian subcontinent is the consequence of the heritage of the antimonials (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, miltefosine (hexadecylphosphocholine [HePC]), an alkylphosphocholine originally developed as an anticancer drug, was proven to be effective and safe for use against visceral leishmaniasis in India (1) and was successfully applied to treat patients infected with antimony-resistant parasites. However, the therapeutic window of this drug might be very short, given the appearance of drug resistance in vitro (2). Thus, in the absence of vaccination and given the limitations of current therapies in cost, efficacy, and safety, there is an urgent need for the identification of novel targets and new chemical entities with antileishmanial activity.…”
mentioning
confidence: 99%
“…New drugs such as miltefosine and amphotericin B are in use for the treatment of antimony-resistant (Sb R ) kala-azar cases, but relapse cases are also increasing (5,6). Because antimonials and miltefosine use the same efflux pump (7), this raises serious concern about the efficacy of miltefosine, either alone or in combination, in view of the rampant antimony resistance in the field. Recent studies from our group showed that ∼78% of the recent clinical isolates are resistant to antimonials although the drug has not been in use for more than a decade in Bihar (8).…”
mentioning
confidence: 99%